Improving household fish and vegetable availability through participation of rural women: A case study - S. Tanuja; A. Sarkar; G. Moharana; C. S. Mhatre (Indian Journal of Fisheries, 2023)
Homestead integrated aquaculture has immense potential towards alleviating poverty andundernourishment. In order to have sustainable and equitable impacts through small holderaquaculture innovations, a focus on gender being included at the very start of the designand dissemination is required. The present case study showcases the impact of genderinclusive interventions in improving the participation of women in homestead aquaculture,thereby improving the household fish and vegetable availability and income. Conservation ofthe diminishing stock of small indigenous fishes by deliberately farming them along with theIndian major carps (IMCs) was also a focus of the study. A gender inclusive approach wasadopted in the capacity building of women on scientific aquaculture management practices.Twenty four homestead ponds having areas ranging from 0.17-0.22 ha in Puri District, Odishacovering a total area of 4 ha from four villages were selected to undertake participatoryaction research. The ponds were stocked with IMCs @10000 ha-1 and small indigenousfishes like Amblyphanrynogon mola and Puntius spp. @25000 ha-1. Several women friendlyinterventions like gillnets (mesh size 12 mm) a passive fishing gear and trellis systemaround pond bund for growing climber vegetables were introduced in the villages with anaim to improve the participation of women in homestead integrated aquaculture. As a resultof the interventions, the fish production increased from 0.75 t ha-1 yr-1 to 2.48 t ha-1 yr-1.The involvement of women in harvesting of small fish using passive gear like gillnets andtraps resulted in regular fortnightly availability of around 750 g of small micronutrient richfish to rural families. The utilisation of pond bund for growing vegetables following thecropping calendar resulted in production around 790 kg vegetables per hectare of pondarea. The study showed that women can immensely contribute to increasing and stabilisingfamily income and in improving family nutrition by participating in homestead integratedaquaculture. The research also proved that polyculture of IMCs with small indigenous fishesby following the scientific management practices will result in better yield, improved fishavailability to the house and better management of the household resources.Keywords: Aquaculture, Empowerment, Household, Horticulture, Participation, Women